Studies on the Effect of Amino Acids to Curb the Pathogenesis of Multi Drug Resistant Staphylococcus aureus - Arya, Rekha; Vinoth Kannan, R.; Shrivastava, Sajal; Adline Princy, S. (Asian Journal of Chemistry, 2011)
The amino acids have been known for their stimulatory and inhibitory effects on the growth and expression of virulent characters such as toxin production, biofilm formation and colony spreading. If the complete mixture of natural amino acids is added to the basal medium, the accumulation of toxins increases, while Staphylococcus aureus was unable to produce toxins in an amino acid deprived medium. Present study suggests that the phenylalnine in all cases inhibits toxin production whereas methionine and serine reduces the biofilm disposition in Staphylococcuss aureus. Employing chemically modified medium with certain amino acids to scrutinize mechanisms of pathogenesis gives rise to the impending for additional clinical benefits beyond providing new insights in this medically pertinent field of study. It is desirable that using biostable peptides that target virulence pathways instead of microbial viability will reduces the chance of adaptability of a pathogen and therefore reduces the chance of resistance developing to a treatment.